THE EFFECTS OF OIL PRICE SHOCK AND EXCHANGE RATE ON GROSS DOMESTIC PRODUCT: EVIDENCE FROM LIBYA - Kraim, Mahmoud (PT. Altin Riset Publishing, 2024)
Many studies have investigated the relationship between oil price shock, exchange rate, and gross domestic product (GDP). This paper examines the effects of an oil price shock and the exchange rate on the GDP in the case of Libya. In this context, we applied the Johansen VAR-based cointegration technique to examine the sensitivity of GDP to the oil prices and exchange rate in the long run. In short-run relationships, we have used the vector error correction estimates (VECM) test through time-series data that included the period between 1990 and 2019. The main finding is that the oil price and exchange rate are important influences on the GDP of Libya. This study has proved that oil prices positively affected the Libyan economy, while we found that the exchange rate harms Libyan GDP.